Employment prospects and skill acquisition of apprenticeship- trained workers in Germany - Winkelmann, Rainer [Verfasser] (My University, 1996)
"Using data from the German Socio-Economic Panel for 1984-90, the author analyzes the entrance of young individuals into the German labor market, comparing the experience of apprenticeship graduates to that of graduates from universities, full-time vocational schools, and secondary schools. Apprentices experienced fewer unemployment spells in the transition to their first ful-time employment than did nonapprentices. Among apprentices, those trained in large firms had the smoothest transition to employment; once employed, however apprentices (whether they stayed in their training firm or not) and nonapprentices had similar job stability (as measured by tenure). An estimated 70% of apprenticeship trainees left their training firm within a five-year period. These findings are consistent with the view that apprenticeship training develops general, portable skills rather than firm-specific skills." (author- s abstract, IAB-Doku) ((en)) Mit den Daten des SOEP analysiert der Autor den Übergang von Absolventen des dualen Systems in den Arbeitsmarkt. Der Vergleich mit Abgängern aus anderen Schulsystemen zeigt die relativ gute Position der Ausbildungsabgänger. Ferner zeigt die Analyse, dass die duale Ausbildung weniger betriebsspezifische als vielmehr allgemein verwertbare Qualifikationen vermittelt. (IAB)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 2.3.1 Arbeitsteilung & -organisation; G 1.3.3.4 Wiedereingliederung; Betriebliche Berufsausbildung; Absolvent; Duales System; Arbeitslosigkeit; Berufliche Integration; Arbeitsmarktchance; Quantitative Angaben; 1984-1990